PARADIGMA GURU DAN ORANGTUA TERHADAP PENERAPAN UNDANG-UNDANG PERLINDUNGAN ANAK DI SEKOLAH - Ahmad Munawir (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2019)
Acts of violence involving students in schools have an impact on the pattern of teacher education and the mindset of parents of students on the education system with the child protection law. Therefore, this study aims at describing the pattern of teacher education and the mindset of students’ parents towards the application of child protection laws in schools. The research used descriptive qualitative research with library research. The results of the study shows that the child protection law has changed the pattern of teacher education and the mindset of parents of students towards the educational process that occurs in schools. The child protection law does not give the freedom for teachers to take decisive action and to give punishment to students; and it is used by the parents of students as a tool to criminalize teachers